Обзор видов рода Sericus Esch. (Coleoptera, Elateridae) фауны СССР - Гурьева, Е.Л. (Вестник зоологии, 1974)
The article contains diagnosis of the genus Serial's E s c h ., the key of palaearctic species, its synonymy and distribution.